Course-Based Undergraduate Research Experiences Can Make Scientific Research More Inclusive - Bangera, Gita (CBE Life Sci Educ, 2014)
Course-based undergraduate research experiences (CUREs) may be a more inclusive entry point to scientific research than independent research experiences, and the implementation of CUREs at the introductory level may therefore be a way to improve the diversity of the scientific community.